DETERMINANTS OF CONSUMER EGG PRICES IN TURKIYE USING K-NEAREST NEIGHBORS REGRESSION ANALYSIS - Cevrimli, M. B.; Mat, B.; Polat, M.; Arikan, M. S.; Akin, A. Cu.; Tekindal, M. A.; Gunlu, A. (Pakistan Agricultural Scientists Forum, 2024)
Examining the factors impacting egg consumer prices in Turkiye holds significant importance. This research contributes to a deeper understanding of how specific variables influence market prices and illuminates cause-and-effect relationships in price fluctuations. The study analyzed 131 datasets from Turkiye, covering the period from January 2010 to November 2020, including various factors. The primary aim was to predict the relationships and impacts on egg consumer prices by considering variables such as laying hens feed price, the exchange rate of the US dollar, producer price indices, agricultural producer price indices, feed prices for broilers, corn, barley, and soybeans, utilizing K-nearest neighbors (KNN) regression analysis. Within the model, the consumer price of eggs showed the weakest correlation with the corn variable (r = 0.832). In contrast, the consumer price of eggs displayed the highest correlation with the US dollar exchange rate and soybean variables (r = 0.892). Therefore, it is evident that egg consumer prices are significantly influenced by the costs of raw materials for feed and currency exchange rates. Unlike other studies, this study found that the price of broiler feed also affects consumer egg prices. Thus, it is imperative for Turkiye to implement policies promoting the local supply of imported inputs essential for egg production and adopt measures to manage and mitigate exchange rate fluctuations and production expenses.
Keywords: Egg; consumer price; laying hens feed price; Dollar exchange rate; Turkiye